Augmenting extinction learning with d-cycloserine reduces return of fear: a randomized, placebo-controlled fMRI study - Ebrahimi, Claudia (Neuropsychopharmacology, 2019)
d-cycloserine (DCS), a partial NMDA-receptor agonist, seems to be a promising enhancer for exposure therapy in anxiety disorders. It has been tested successfully in animal models of fear extinction, where DCS enhanced extinction learning. Applied in clinical studies, results of DCS-augmented exposure therapy remain ambiguous, calling for a deeper understanding of the underlying mechanisms of DCS and its exact effect on extinction learning and return of fear (ROF) in humans. In the present study, we investigated the effect of DCS-augmented extinction learning on behavioral, psychophysiological, and neural indices of ROF during a 24-h delayed recall test. Thirty-seven participants entered a randomized, placebo-controlled, double-blind, 3-day fear conditioning and delayed extinction fMRI design. One hour before extinction training, participants received an oral dose of 50 mg of DCS or a placebo. Behavioral arousal ratings revealed a generalized ROF during extinction recall in the placebo but not DCS group. Furthermore, participants receiving DCS compared to placebo showed attenuated differential BOLD responses in left posterior hippocampus and amygdala from extinction learning to extinction recall, due to increased hippocampal recruitment in placebo and trendwise decreased amygdala responding in DCS subjects. Our finding that DCS reduces ROF in arousal ratings and neural structures subserving defensive reactions support a role for NMDA receptors in extinction memory consolidation and encourage further translational research.